Development and validation of a nomogram to predict survival for advanced male breast cancer - Zhang, Li‐Ping; Lin, Hui; Wang, Ai‐Jing (Andrologia, 2022)
Male breast cancer is a rare disease. Many experiences of male breast cancer were derived of female breast cancer. However, there are huge differences between two groups. We conducted this study to find a reliable prognostic model for advanced male breast cancer. The cohort was selected from the Surveillance, Epidemiology, and End Results database. The enrolled patients were randomly divided into training and validation group. The univariate and multivariate analyses were used for prognostic assessment and a nomogram was built. Calibration curves and concordance index were compiled to determine predictive and discriminatory capacity. The time‐dependent receiver operating curves and the decision curve analysis was used to verify the model's ability. Two hundred and eighty individuals were enrolled. The cumulative rates of 1‐, 3‐ and 5‐year overall survival (OS) rates were 98.6%, 72% and 57.9%. The C‐indexes for OS were 0.835 (95%CI, 0.777–0.893) in the training group and 0.765 (95%CI, 0.668–0.862) in the validation group. The calibration curves confirmed the consistency of the nomogram both in the training and validation group. The time‐dependent receiver operating curves and decision curve analysis demonstrated that the nomogram had better prediction capacity than TNM stage system for advanced male breast cancer. The nomogram we built was a reliable and solid predictive model.